The First International Research Conference on Carbon Pricing - Carbon Pricing Leadership Coalition (World Bank, Washington, DC, 2019)
This report provides the papers and proceedings of the first International Research Conference on Carbon Pricing held from February 14-15, 2019 in New Delhi, India. With the goal of strengthening the carbon pricing knowledge base and fostering an improved understanding of the evolving challenges to its successful application, the Carbon Pricing Leadership Coalition convened researchers, practitioners, and interested stakeholders for the CPLC Research Conference.